2010
DOI: 10.1176/appi.ajp.2010.09060877
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Antidepressant Step Therapy Protocols on Pharmaceutical and Medical Utilization and Expenditures

Abstract: Step therapy may have the unintended effect of reducing overall antidepressant use and increasing medical use and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
52
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(53 citation statements)
references
References 14 publications
1
52
0
Order By: Relevance
“…25 Mark et al (2009) examined total prescription drug expenditures for antihypertensive users (i.e., not just antihypertensive spend) and reported that overall prescription drug spending initially declined 3.1% after program implementation, but the savings did diminish somewhat over time. 12 The authors did not report changes in antihypertensive drug spending. Motheral et al (2004) found drug savings of $0.93 PMPM following implementation of an ST program for PPIs, NSAIDs, and selective serotonin reuptake inhibitors (SSRIs).…”
Section: ■■ Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…25 Mark et al (2009) examined total prescription drug expenditures for antihypertensive users (i.e., not just antihypertensive spend) and reported that overall prescription drug spending initially declined 3.1% after program implementation, but the savings did diminish somewhat over time. 12 The authors did not report changes in antihypertensive drug spending. Motheral et al (2004) found drug savings of $0.93 PMPM following implementation of an ST program for PPIs, NSAIDs, and selective serotonin reuptake inhibitors (SSRIs).…”
Section: ■■ Methodsmentioning
confidence: 99%
“…[8][9][10] ■■ Results Fourteen evaluations of ST programs have been published to date. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] Seven of the studies were conducted in commercial populations (Table 1), while 7 assessed Medicaid ST programs (Table 2). An analysis by Panzer et al (2005) was an economic model of an antidepressant ST program for patients with anxiety, 15 and Cox et al (2004) surveyed members with an ST edit/ reject to assess their responses to the edit.…”
Section: ■■ Methodsmentioning
confidence: 99%
See 3 more Smart Citations